Deformation characteristics and fluid-solid coupled analysis of a super-deep circular foundation pit in soft soils - Xin MA; Dean SUN; Shujia LIU (Shuiwen dizhi gongcheng dizhi)
The characteristics of super-deep circular foundation pit project in soft soil area are complexity, dangers, and scarcity. It is of great significance to simulate and predict its deformation accurately. As to the super-deep circular pit with excavation depth of 56.3 m in the deep tunnel project of Suzhou River in Shanghai, a fluid-solid coupled finite element analysis model based on the Biot consolidation theory was established. The deformation and force characteristics of super-deep circular foundation pits in soft soil areas were investigated by combining the actual monitoring data. The difference in mechanism between the fluid-solid bidirectional coupling analysis (BCA) and the unidirectional coupling analysis (UCA) which is commonly used in engineering to consider the single effect of the seepage field on the soil skeleton, as well as the difference between the calculation results of the two analysis and the actual monitoring data were analyzed. The results show that the lateral displacement on the side of the circular retaining structure subjected to large bias load increases by 64.7% compared with that on the side not subjected to bias load, indicating an obvious spatial effect. The fluid-solid coupling analysis can predict the deformation of the soil and the retaining structure effectively because it considers the process that water is gradually discharged from the pore with time, and then the excess pore pressure is gradually dissipated with the change of the volume of the soil. For the maximum lateral displacement of the retaining structure, the errors between measured and calculated values of the UCA and BCA are 42.35% and 14.35%, respectively. Regarding the maximum circumferential axial force, the errors between the measured and calculated values for UCA and BCA are 14.30% and 10.27%, respectively. The results of foundation deformation and internal force obtained from the BCA are better than UCA. This study can provide the basic information for the design and construction of circular super-deep foundation pits in soft soil areas.